Impact of Personality Measures and Investors’ Biases on Decision - Making Skills of Women Investors in Mutual Funds - Ramesh, S.; Senthil Kumar, A.; Sayyed, Nasreen (Indian Journal of Finance, 2019)
Mutual funds (MFs) have grown to be a main vehicle for mobilization of savings, especially from the small and household sector for investment in the stock market, which ensures high returns and low risk. Indian investors are peculiar in nature, and it is tough to predict their behaviour as they belong to different cultures, religions, lifestyles, social status, education levels, and income groups. The study was conducted with the aim of analyzing the impact of personality measures and investors’ biases on decision-making skills of women investors in mutual funds. The data were collected from 270 women investors who were living in Chennai city, Tamil Nadu through questionnaires in the year 2017 - 18. The opinion of women investors was gathered through a 5-point scale on the impact of personality traits and investors’ biases on decision to invest in mutual funds. Confirmatory factor analysis method was used for data analysis. The study revealed that investors’ biases had a great impact on the decision-making skills of women investors and there was a statistically significant indirect effect of personality measures on decision-making skills through investors’ biases.